2020
DOI: 10.1007/jhep07(2020)182
|View full text |Cite
|
Sign up to set email alerts
|

Quantum soliton scattering manifolds

Abstract: We consider the quantum multisoliton scattering problem. For BPS theories one truncates the full field theory to the moduli space, a finite dimensional manifold of energy minimising field configurations, and studies the quantum mechanical problem on this. Non-BPS theories -the generic case -have no such obvious truncation. We define a quantum soliton scattering manifold as a configuration space which satisfies asymptotic completeness and respects the underlying classical dynamics of slow moving solitons. Havin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This suggests that size fluctuations are low energy excitations and should be included in any two-skyrmion configuration space. An analogous mode can be seen in the baby Skyrme model, where it can be understood in terms of rational map solutions of the nonlinear sigma model [12]. The pairing of perturbations can be understood by considering the symmetry of the torus.…”
Section: The N=2 Instanton-generated Skyrmionsmentioning
confidence: 92%
See 3 more Smart Citations
“…This suggests that size fluctuations are low energy excitations and should be included in any two-skyrmion configuration space. An analogous mode can be seen in the baby Skyrme model, where it can be understood in terms of rational map solutions of the nonlinear sigma model [12]. The pairing of perturbations can be understood by considering the symmetry of the torus.…”
Section: The N=2 Instanton-generated Skyrmionsmentioning
confidence: 92%
“…The 2-skyrmion configuration space should contain degrees of freedom which describe two well separated skyrmions, and hence it should be at least 12-dimensional. Recently, it was shown that two skyrmions with equal initial sizes can change their relative size after scattering [12]. Hence size fluctuations are low energy excitations and should be included in the configuration space.…”
Section: Jhep12(2021)039mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a rather nice way to graphically represent the phase of a baby Skyrmion [34] using a HSV color model, which is almost analogous to the Runge color sphere coloring in the Skyrme model. We begin by plotting the energy density and color it using the stereographic coordinate W , given in (13).…”
Section: A Standard Baby Skyrmionsmentioning
confidence: 99%